Physical fitness in scholchildren in Aracaju - Silvan Silva de Araujo; Antônio César Cabral de Oliveira (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p271 This study aimed to describe the health-related physical fitness of adolescents from public schools in the city of Aracaju, SE, Brazil, and the effects of growth and maturation on physical variables. The sample was composed of 288 elementary school students, 146 of whom were male and 142 female, aged between 10 and 14 years. The following variables were measured: body mass, height, flexibility, muscle strength/endurance and aerobic capacity. Descriptive statistics and Student's t test for independent samples were used for data analysis, adopting a 5% significance level (p <0.05). When the results from the two sexes were compared, significant low variations were observed, always in favor of the males, in all variables with the exception of abdominal strength at 11, 12 and 13 years of age, strength/resistance of arms at 12 years and aerobic capacity (VO2max) at 10, 12 and 14 years, for all of which differences were not significant. Sexual maturity only had na effect on flexibility in males and VO2 max in both sexes.